Effects of alcoholic extract of Myristica fragrans (nutmeg) on pregnancy outcome in female Wistar rats - C.L. Sakpa; D.O. Eguavoen (Journal of Applied Sciences and Environmental Management, 2021)
Myristica fragrans has been reported to be a medicinal plant as it possesses hepatoprotective, antimicrobial, anti-oxidant, antiulcer, anticancer and immunostimulatory properties, as well as antifertility potentials. This study therefore aimed to investigate the effects of alcoholic extract of M. fragrans on dam size, litter size, pup weight, ovarian follicles, endometrial glands and histopathological indices on pregnancy outcomes in female Wistar rats using standard methods. Pregnancy was induced in forty-eight (48) female Wistar rats that were randomly selected and assigned into four (4) groups of twelve (12) rats each: Group 1 (pregestational phase of pregnancy), Group 2 (germinal phase of pregnancy), Group 3 (embryonic phase of pregnancy) and Group 4 (Fetal phase of pregnancy). The treated animals all received 1500 mg of alcoholic extract of M. fragrans. Administration of distilled water and the extract was by orogastric tube. Data were subjected to statistical analysis using the IBM SPSS statistics software (Statistical Package for Social Science) (Version 25) and relevant statistical values were obtained. The extract prevented the proliferation of ovarian follicles and endometrial glands. In addition, during the pregestational, germinal and embryonic phases, there were significant increases in weight of pups when the treated animals were compared to the control group. The dams also showed decreases in body weight during the embryonic phase. This study therefore demonstrated that alcohol extract of Myristica fragrans may serve as a contraceptive agent in view of its anti-fertility effect.